Coronary perforation complicating percutaneous coronary intervention in patients presenting with an acute coronary syndrome: An analysis of 1013 perforation cases from the British Cardiovascular Intervention Society database. (15th January 2020) - Kinnaird, Tim; Kwok, Chun Shing; Davies, Rhodri; Calvert, Patrick A.; Anderson, Richard; Gallagher, Sean; Sirker, Alex; Ludman, Peter; deBelder, Mark; Stables, Rod; Johnson, Thomas W.; Kontopantelis, Evan; et al.
Abstract: Background: The evidence base for coronary perforation occurring during percutaneous coronary intervention in patients presenting with an acute coronary syndrome (ACS-PCI) is limited and the specific role of acute pharmacology in its clinical presentation unclear. Methods and results: Using the BCIS PCI database, data were analysed on all ACS-PCI procedures performed in England and Wales between 2007 and 2014. Multiple regressions were used to identify predictors of coronary perforation and its association with outcomes. Propensity score matching was used to evaluate the association between differing P2Y12 inhibitors or glycoprotein inhibitors (GPI) and CP. During 270, 329 ACS-PCI procedures, 1013 coronary perforations were recorded (0.37%) with a stable annual incidence. In multiple regression analysis, covariates associated with increased frequency of coronary perforation included age, female gender, CTO intervention, number and length of stents used, and rotational atherectomy use, whilst differing P2Y12 inhibitors were not predictive. Using propensity score matching, use of a GPI was independently associated with tamponade (OR 1.50, [1.08–2.06], p  = 0.014). The adjusted odds ratios for all clinical outcomes were adversely affected by coronary perforation. Conclusions: Coronary perforation is an infrequent event during ACS-PCI but is closely associated with adverse clinical outcomes. GPI use was associated with higher rates of tamponade. Highlights: Data were analysed on all UK ACS-PCI procedures between 2007 and 2014. Of 270, 329 ACS-PCI procedures, 1013 coronary perforations occurred (0.37%). Covariates associated with CP included age, female sex, rotablation and CTO PCI. Use of a glycoprotein inhibitor was independently associated with tamponade. All clinical outcomes were adversely affected by coronary perforation.